A Receptor-Oriented Approach to Overcoming Universal Challenges in Science Education - Goshu, Belay Sitotaw; Ridwan, Muhammad (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2024)
This study explores key challenges in science education from a receptor-oriented perspective, analyzing the experiences of teachers, students, school administrators, policymakers, and community stakeholders. Findings reveal significant barriers, including inadequate resources, limited professional development for teachers, low student engagement, outdated curricula, and insufficient policy support. Teachers reported a lack of access to necessary resources and training in emerging science topics, which limits their ability to conduct hands-on, inquiry-based lessons. Students expressed a desire for more relevant, real-world applications in science, which are missing due to curriculum rigidity and emphasis on standardized testing. Furthermore, administrators identified funding constraints and digital illiteracy as obstacles to implementing modern science education. Community and industry involvement was identified as crucial yet underutilized, limiting students' exposure to STEM career pathways and practical science applications. The findings underscore the need for reform strategies that provide resource allocation, updated curricula, reduced testing pressures, digital literacy initiatives, and structured partnerships with industry. A receptor-oriented approach is recommended to tailor solutions for each group’s unique needs, ultimately supporting a more engaging, equitable, and future-focused science education system.